2007
DOI: 10.1002/ppap.200700032
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Processing of Propane at Hyper‐Atmospheric Pressure: Experiment and Modelling

Abstract: A dielectric packed‐bed plasma reactor was used for the destruction of propane in air and was successfully created and maintained at higher than atmospheric pressure (3 bar). The effects of pressure, REF and SED on propane removal and NOx production are discussed. An increase in SED enhances propane destruction and increases NOx production. Increasing the pressure to 3 bar produces a more efficient removal process with an energy of 877 and 600 eV per molecule at 1 and 3 bar, respectively. The pressure increase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 15 publications
1
12
0
Order By: Relevance
“…The only way to describe these results is to consider reactions (3) and (4) as purely dissociative processes, i.e. followed by (5). This approach is also consistent with results obtained about by-products, discussed in the following section.…”
Section: Role Of Metastable States Of Nitrogen In the Removal Of Propanesupporting
confidence: 73%
See 1 more Smart Citation
“…The only way to describe these results is to consider reactions (3) and (4) as purely dissociative processes, i.e. followed by (5). This approach is also consistent with results obtained about by-products, discussed in the following section.…”
Section: Role Of Metastable States Of Nitrogen In the Removal Of Propanesupporting
confidence: 73%
“…The kinetic of propane in non-thermal plasmas of atmospheric gases (N 2 /O 2 /H 2 O mixtures) is currently under study owing to various applications such as cleaning of polluted air streams [1][2][3][4][5][6], or more recently plasma assisted ignition and combustion [7][8][9][10][11][12][13]. Owing to other types of previously developed applications of low pressure plasmas, for example carbon compounds thin films production [14], numerous works have been performed in the past about electron collisions on this hydrocarbon molecule [15][16][17][18], especially on ionisation processes.…”
Section: Introductionmentioning
confidence: 99%
“…Conversely, Martin et al were able to process propene in dry air with an initial NO concentration of 500 ppm without the formation of methyl nitrate. We have previously reported that during DBD processing of propane in air, nitrate and nitrite production is unimportant. This may be due to the difference in available NO and NO 2 ; Dorai and Kushner 10 use an initial NO concentration of 260 ppm, while our previous work 17 and the current work do not add NO to the gas stream, and thus the NO x available for reaction is only what is created in the air plasma discharge.…”
Section: Resultsmentioning
confidence: 99%
“…The mechanisms for oxidative plasma decomposition of propane and propene are well established. 10,11,13 The reaction of atomic oxygen proceeds via hydrogen atom abstraction…”
Section: Discussionmentioning
confidence: 99%
“…This value was then used in all of the simulations. The reaction mechanism was adapted from that used in Hill et al; 11 the majority of the breakdown routes for propane and propene follow the same pathways. However, additional reactions were needed to describe the initial breakdown of propene by the primary and secondary active species formed in the plasma.…”
Section: Modelingmentioning
confidence: 99%